2019
DOI: 10.3390/v11040365
|View full text |Cite
|
Sign up to set email alerts
|

Activity of Selected Nucleoside Analogue ProTides against Zika Virus in Human Neural Stem Cells

Abstract: Zika virus (ZIKV), an emerging flavivirus that causes neurodevelopmental impairment to fetuses and has been linked to Guillain-Barré syndrome continues to threaten global health due to the absence of targeted prophylaxis or treatment. Nucleoside analogues are good examples of efficient anti-viral inhibitors, and prodrug strategies using phosphate masking groups (ProTides) have been employed to improve the bioavailability of ribonucleoside analogues. Here, we synthesized and tested a small library of 13 ProTide… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Recently, the clinically approved HCV nucleoside analogue ProTide 5 (sofosbuvir) was the subject of several studies demonstrating its efficacy and safety as an anti-ZIKV compound in neural cell lines and in vivo mouse models of infection (including prevention of ZIKV vertical transfer), with a reduction in the severity of disease and mortality associated with dosing of the drug in the latter system. Recent in vitro studies of related nucleoside analogue ProTides have revealed that 2′- C -methyl and 2′- C -ethynyluridine aryoxyl phosphoramidate ProTides ( 6 and 7 ) show improved anti-ZIKV activity compared to sofosbuvir . The authors note both a nucleobase and ProTide masking group bias in compound activity, the basis of which remains to be explored mechanistically.…”
Section: Drug Discovery Initiativesmentioning
confidence: 99%
“…Recently, the clinically approved HCV nucleoside analogue ProTide 5 (sofosbuvir) was the subject of several studies demonstrating its efficacy and safety as an anti-ZIKV compound in neural cell lines and in vivo mouse models of infection (including prevention of ZIKV vertical transfer), with a reduction in the severity of disease and mortality associated with dosing of the drug in the latter system. Recent in vitro studies of related nucleoside analogue ProTides have revealed that 2′- C -methyl and 2′- C -ethynyluridine aryoxyl phosphoramidate ProTides ( 6 and 7 ) show improved anti-ZIKV activity compared to sofosbuvir . The authors note both a nucleobase and ProTide masking group bias in compound activity, the basis of which remains to be explored mechanistically.…”
Section: Drug Discovery Initiativesmentioning
confidence: 99%
“…ZIKV replication in cell culture is also affected by a variety of inhibitors of pyrimidine biosynthesis, such as brequinar and CID 91632869 [108], which effect may be due not to pyrimidine privation but to cellular immune response induction [116,145]. Gemcitabine [107,117], although its use may result in damage to the fetus, 2′-2′-C-methylcitosine, 2′-C-methyluridine [118], and their proTides [118], 5-fluorouracil, an anticancer drug, 6-azauridine, an antineoplastic, and finasteride, used in patients with enlarged prostate [97,108,119], also reduce virus multiplication. However, the clinical use of these last two may be impaired by their low solubility.…”
Section: Antiviralsmentioning
confidence: 99%
“…In in vitro studies, EC 50 values of 7DMA varied from 1.2 to 9.6 μM . Other 2′-C-methylated derivatives (2′-C-methyladenosine, cytidine, and uridine) have also exhibited activity against ZIKV, albeit with EC 50 values in the midmicromolar range. , …”
mentioning
confidence: 99%
“…Recently, Bernatchez and co-workers reported that 2-(methylthio)­ethyl-2′-C-β-uridine tryptamine phosphoramidate diester was inactive against ZIKV in a cell-based in vitro model of ZIKV infection . However, anti-ZIKV activity was observed with an aryloxyl phosphoramidate derivative of 2′-C-β-uridine.…”
mentioning
confidence: 99%